Guaman Poma’s Paper Trail: Word and Image in the New Chronicle - Harrison, Regina (2020)
As a translator, a witness, and a litigant, Guaman Poma well serves to describe the implementation of Spanish administrative and juridical institutions in colonial Peru. In lettered texts, as well as in black andwhite drawings found in his Nueva Corónica, Guaman Poma references the paper artifacts of Spanish juridical processes in his project to preserve native Andean cultural practices and properties. This essay examines his knowledge of legal processes, legal formats, and his program for a legacy of justice in the Andes. In closely studying exemplary texts such as the writ of amparo, cédula (decree) and permuta (exchange), Guaman Poma uses Spanish law for his Andean purposes. With attention to previous research by Adorno, Quispe-Agnoli, de la Puente Luna, and Burns, this study examines concepts of European law and history deemed advantageous for native Andeans.